New insights into the Enchytraeus albidus complex (Annelida, Enchytraeidae), with the description of three new species from seashores in Italy and Croatia - Nagy, Hajnalka; Dózsa-Farkas, Klára; Felföldi, Tamás (European Journal of Taxonomy, 2023)
Between 2019 and 2021, samplings were carried out from seashores in Italy and Croatia, where specimens were found morphologically similar to the species of the Enchytraeus albidus complex. The taxon Enchytraeus albidus was recently divided into a number of separate species, and the new Italian and Croatian specimens of Enchytraeus proved to be three additional species, all new to science, based on the results of morphological and molecular studies. In this paper, we present the description of these new species, namely Enchytraeus adrianensis sp. nov., Enchytraeus andrasi sp. nov. and Enchytraeus andrasiformis sp. nov., and provide additional morphological data and new reference sequences for E. albidus s. str., E. krumbachi, E. irregularis and further unidentified specimens that belong to the E. albidus group collected formerly from Hungary, Korea, Svalbard and Kerguelen Islands.